EFEK TEKANAN PADA PERFORMANSI PEMANAS AIR TENAGA SURYA SISTEM PIPA PANAS DENGAN FLUIDA KERJA R718 - Himsar Ambarita (Jurnal Teknik Kimia USU, 2017)
In this work a heat pipe type solar water heater using R178 as a refrigerant is studied experimentally. The objective is to investigate the effect of initial vacuum pressure on the performance of the solar water heater. An experimental apparatus that consists of three difference solar water heaters has been designed and fabricated. The heat pipe is filled with R178 and vacuumed at an initial pressure. The pressure is varied from 35 cm Hg, 40 cm Hg, and 45 cm Hg. The experimental apparatus is tested by exposing to solar irradiance in Medan city of Indonesia. The experiments are carried out for three different days. The averaged solar intensity at the first, second and third experiments are 497.76 W/m2, 405.27 W/m2, and 333.83 W/m2, respectively. The results show that maximum temperature of the hot water varies from 51.14oC and 62.22oC. In the first experiment, thermal efficiency of the solar water heater at initial vacuum pressure 35 cm Hg, 40 cm Hg, and 45 cm Hg are 30,94%, 32,01% and 34,38%, respectively. The similar trends are also shown in the second and third experiments. These facts suggest that R178 can be used as a refrigerant in a heat pipe solar water heater with a good performance. The higher vacuum initial pressure of the heat pipe results in higher thermal efficiency. The higest thermal efficiency of the present study is 45.92%. It occurs at initial pressure and average irridiance of 45 cm Hg and 333.83W/m2.